Association study of 25 type 2 diabetes related Loci with measures of obesity in Indian sib pairs. - Vipin Gupta; Donipadi Guru Vinay; Ulla Sovio; Sajjad Rafiq; Madamchetty Venkata Kranthi Kumar; Charles Spurgeon Janipalli; David Evans; Kulathu Radha Mani; Madana Narasimha Sandeep; Amy Taylor; Sanjay Kinra; Ruth Sullivan; et al. (PLoS ONE)
Obesity is an established risk factor for type 2 diabetes (T2D) and they are metabolically related through the mechanism of insulin resistance. In order to explore how common genetic variants associated with T2D correlate with body mass index (BMI), we examined the influence of 25 T2D associated loci on obesity risk. We used 5056 individuals (2528 sib-pairs) recruited in Indian Migration Study and conducted within sib-pair analysis for six obesity phenotypes. We found associations of variants in CXCR4 (rs932206) and HHEX (rs5015480) with higher body mass index (BMI) (β=0.13, p=0.001) and (β=0.09, p=0.002), respectively and weight (β=0.13, p=0.001) and (β=0.09, p=0.001), respectively. CXCR4 variant was also strongly associated with body fat (β=0.10, p=0.0004). In addition, we demonstrated associations of CXCR4 and HHEX with overweight/obesity (OR=1.6, p=0.003) and (OR=1.4, p=0.002), respectively, in 1333 sib-pairs (2666 individuals). We observed marginal evidence of associations between variants at six loci (TCF7L2, NGN3, FOXA2, LOC646279, FLJ39370 and THADA) and waist hip ratio (WHR), BMI and/or overweight which needs to be validated in larger set of samples. All the above findings were independent of daily energy consumption and physical activity level. The risk score estimates based on eight significant loci (including nominal associations) showed associations with WHR and body fat which were independent of BMI. In summary, we establish the role of T2D associated loci in influencing the measures of obesity in Indian population, suggesting common underlying pathophysiology across populations.